A Particular SORL1 Micro-haplotype May Prevent Severe Liver Disease in a French Cohort of Alpha 1-Antitrypsin-deficient Children. Issue 3 (September 2021) - Joly, Philippe; Ruiz, Mathias; Garin, Roman; Karatas, Esra; Lachaux, Alain; Restier, Lioara; Belmalih, Abdelouahed; Renoux, Céline; Lombard, Christine; Dechomet, Magali; Bouchecareilh, Marion
Abstract : ABSTRACT: The presence of modifier genes is now well recognized in severe liver disease outcome associated with alpha-1-antitrypsin deficiency (A1ATD) but their identification remains to be fully elucidated. To address this goal, we performed a candidate gene study with the SORL1 gene, already identified as risk gene in early-onset Alzheimer Disease families. A particular SORL1 micro-haplotype constituted with 3 SNPs (wild-type form TTG) was genotyped on 86 ZZ A1ATD children issued from 66 families. Interestingly, the mutated forms of this micro-haplotype (CAT most of the time) were associated with lower occurrence of severe liver disease and in cellulo studies showed that SORL1 influences Z-A1ATD cellular toxicity and biogenesis. These data suggest that the mutated CAT form of SORL1 micro-haplotype may partly prevent from severe liver disease in A1ATD children. Overall, these findings support a replication study on an independent cohort and additional in cellulo studies to confirm these promising results. Abstract : Supplemental Digital Content is available in the text